Coupled mechanical resonators with broken Lorentz reciprocity for sensor applications - Lijie Li (Mechanical Systems and Signal Processing, 2019)
Having simultaneously a high quality factor (i.e. a narrow resonant band) and a shorter decay time between the resonating system and the external sources (i.e. a wide resonant band) is a desirable characteristic for mechanical resonators, which however has been regarded as contradictory. This has been known as the limit of Lorentz reciprocity. We explore a configuration to achieve this desired characteristic within the mechanical regime. The configuration consists of a pair of mechanical resonators coupled together through their connecting part. One of them is encapsulated in a vacuum environment, and the other is left in the normal ambient condition. Numerical model of this configuration shows clearly the advantages such as: (a), sensitivity to the change of resonant frequency is greatly improved (the product of bandwidth and the decay time has increased at least two orders of magnitude); (b), the value of can be adjusted through the coupling stiffness.